THE EFFECTIVENESS OF FLYTRAP WITH ELECTRIC CURRENT IN REDUCING THE DENSITY OF FLIES IN THE MARKET - Adnindya Krismahardi; Rizky Aulia Salsabila Al Mukti; Firdaus Wulan Saputri; Cantika Diah Berliana; Raventi Dyah Pramilena (Buletin Keslingmas, 2020)
Vector control needs to be done so that the environment is healthy and free from disease. Flies are one of the vectors for diseases such as diarrhea. Parts of flies that can play a role in disease transmission are legs, wings, body hair, feces and vomit. Flies like habitats with poor sanitation are very attracted to bad smells, piles of wet garbage, vegetables, and scraps of meat, this condition can be described by market conditions. The sweet market in Purwokerto can be a potential place for disease spread. This study aims to determine the effectiveness of fly traps with electric current in reducing fly density in Pasar Manis, West Purwokerto District, Banyumas Regency. This type of research is research and development to develop and test tools and to determine the effectiveness of tools in reducing fly density. Samples were taken non-randomly, namely at TPS, loss of meat and storage of vegetables. The data analysis used was univariate to calculate the effectiveness of using the Flaytrap With Electric Current tool and bivariate analysis using the paired T test to determine differences in fly density before and after treatment. The results of the study obtained a sig value (P-value) of 0.004. The sig value shows that the sig value. (P-Value) α (0.05), so there is a significant difference between the results of measurements of fly density before and after treatment using Flytrap with Electric Current and the efficiency of the tool in reducing fly density by 42.87%. For further research, it is necessary to add attractants with strong odors so that they can attract flies into the trap.